Fiber reinforced concrete and preparation method thereof
By using fiber-reinforced concrete on the concrete slope protection wall, combined with the hydrophobic, thermal and electrical conductivity characteristics of the modified aggregate and fiber, the problems of algae adhesion and corrosion are solved, the friction and strength of the slope protection wall are improved, and the service life is extended.
Patent Information
- Application Number
- CN202310062406.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-16
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-01-16
AI Technical Summary
The concrete slope protection wall is prone to algae adhesion and corrosion under the long-term erosion of river water, resulting in a decrease in strength and affecting service life.
By using fiber-reinforced concrete, the surface of the aggregate is modified to coat hydrophobic titanium dioxide and reinforced fibers, combined with the bonding effect of silicon acrylic emulsion, the hydrophobicity and roughness of the concrete surface are improved, the structural density is enhanced, and carbon fiber and basalt fiber are used. Thermal and electrical conductivity accelerate algae death and prevent acidic corrosion.
It is achieved that the concrete surface is not easy to adhere to algae, maintain high friction and mechanical strength, extend service life, and effectively prevent the corrosion of algae on concrete.
Smart Images

Figure BDA0004061411400000081 
Figure BDA0004061411400000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of concrete, and more particularly, to a fiber reinforced concrete and a preparation method thereof. Background Art
[0002] River bank protection generally uses concrete as the pool wall, which has good durability, stability and wind and wave resistance.
[0003] However, the concrete slope protection wall needs to have high strength to ensure that the concrete can still have good stability during long-term river scouring; and the concrete slope protection wall needs to have a certain friction. When people need to clean up the dirt in the river, its high friction can protect the workers walking on the slope protection wall to safely reach the bottom of the river, thereby facilitating the cleaning of impurities and dirt in the river.
[0004] However, the higher friction can easily increase the surface roughness of the concrete. The higher roughness can easily promote the attachment of algae such as algae in river water to the concrete surface. The algae can easily produce acidic substances during metabolism on the surface of cement concrete, which can easily corrode the cement concrete. The strength of the corroded cement concrete itself is reduced, which affects the service life of the river bank protection concrete.
[0005] Therefore, how to make the surface of the slope protection concrete have good friction while making it difficult for algae and other substances to adhere to the concrete surface, so as to ensure that the concrete of the river slope protection still has high strength under long-term use conditions. Summary of the invention
[0006] In order to make the surface of the slope protection concrete have better friction while preventing algae and other substances from adhering to the concrete surface, thereby ensuring that the concrete of the river slope protection still has high strength under long-term use conditions, the present application provides a fiber reinforced concrete and a preparation method thereof.
[0007] In a first aspect, the present application provides a fiber reinforced concrete, which adopts the following technical solution:
[0008] A fiber reinforced concrete is made of the following raw materials in parts by weight: 200-260 parts of cement, 800-1000 parts of modified aggregate, 100-140 parts of water, 5-10 parts of accelerator, 4-6 parts of water reducer, 10-18 parts of reinforcing fiber and 10-20 parts of filler; the modified aggregate is made by coating the surface of the aggregate with hydrophobic titanium dioxide.
[0009] By adopting the above technical scheme, modified aggregates and reinforcing fibers are matched, and the hydrophobic effect of hydrophobic titanium dioxide on the surface of aggregates is utilized to make the surface of concrete hydrophobic and anti-fouling, and it is not easy for algae to attach to the surface of concrete; and titanium dioxide has good roughness, and after attaching to the surface of aggregates, it can further improve the roughness of the surface of aggregates. Aggregates are the raw materials added in the largest amount in concrete, and the higher roughness of aggregates can improve the roughness of the surface of concrete, thereby making the surface of concrete have higher friction; at the same time, the addition of reinforcing fibers and the filling effect of hydrophobic titanium dioxide on the surface of modified aggregates further improve the density of concrete structure, so that concrete has higher strength; even if the slope protection concrete is used for a long time, algae substances are still not easy to attach to the surface, thereby ensuring the mechanical strength of the concrete, and it has good friction, which can ensure the stable movement of people on the surface of the slope protection concrete.
[0010] Preferably, the modified aggregate is prepared by the following method:
[0011] Titanium dioxide is weighed in a mass ratio of 1:3-5 and added to a silicone-acrylic emulsion, and the mixture is stirred evenly to obtain hydrophobic titanium dioxide; the hydrophobic titanium dioxide is sprayed evenly onto the surface of the aggregate, and the mass ratio of the hydrophobic titanium dioxide to the aggregate is 1-5:100; and the finished product is obtained after drying and dispersion.
[0012] By adopting the above technical scheme, titanium dioxide, silicone-acrylic emulsion and aggregate are matched, and the bonding effect of silicone-acrylic emulsion is utilized to make titanium dioxide bonded to the surface of aggregate. Combined with the hydrophobicity and anti-fouling properties of silicone-acrylic emulsion, on the one hand, it can prevent moisture in the river channel from entering into the concrete and affecting the strength of the concrete. On the other hand, even if the slope concrete comes into contact with algae substances, the anti-fouling effect combined with the impact effect of the river water flowing in the river channel can prevent the algae from adhering to the concrete surface, thereby ensuring the mechanical strength of the concrete.
[0013] The mass ratio of hydrophobic titanium dioxide to aggregate is limited so that the hydrophobic titanium dioxide is bonded to the surface of the aggregate without affecting the bonding effect between the aggregate and the cement slurry. In addition, the titanium dioxide adhered to the surface of the aggregate can further increase the roughness of the aggregate, thereby increasing the bonding density between the cement and the aggregate, and making the concrete have higher strength.
[0014] Preferably, the reinforcing fibers are composed of modified carbon fibers and modified basalt fibers in a mass ratio of 1:1-3.
[0015] By adopting the above technical scheme, modified carbon fiber and modified basalt fiber are matched together, and the higher strength of carbon fiber and basalt fiber is utilized, the mechanical strength of concrete can be improved. In addition, the thermal conductivity of carbon fiber is utilized. When sunlight shines on the surface of slope protection concrete, the heat conduction effect of carbon fiber on the surface of concrete is utilized to increase the surface temperature of concrete. The temperature increase can accelerate the death rate of algae, thereby minimizing the metabolism of algae on the surface of concrete to produce acid and affect the strength of concrete. At the same time, carbon fiber can improve the cathodic protection effect by utilizing its conductive effect, and minimize the corrosion of steel bars in concrete caused by acid produced by algae and acid pollution in river water.
[0016] Preferably, the modified carbon fiber is prepared by the following method:
[0017] After hot melting the rosin glycerol ester, a rosin glycerol ester melt is obtained;
[0018] The graphene is evenly dispersed in a rosin glycerol ester melt at a mass ratio of 1:4-7 to prepare a composite liquid;
[0019] The composite liquid is uniformly sprayed onto the surface of the carbon fiber at a mass ratio of 1:2-5, and the modified carbon fiber is obtained after drying and dispersion.
[0020] By adopting the above technical scheme, rosin glycerol ester, graphene and carbon fiber are matched, and the good viscosity of rosin glycerol ester after hot melting is used to make graphene bonded to the surface of carbon fiber, and the lipophilic and hydrophobic properties of rosin glycerol ester are used to make it difficult for algae to adhere to the modified carbon fiber even if it is exposed on the concrete surface; and the graphene and carbon fiber are matched to further conduct heat in the hot summer, and try to prevent the algae attached to the concrete surface from metabolizing and producing acid to affect the surface strength of the concrete; at the same time, graphene is conductive, and combined with carbon fiber, it can further protect the steel bars in the slope concrete from being corroded by acidic substances, thereby ensuring that the concrete has a high strength.
[0021] Preferably, the modified basalt fiber is prepared by the following method:
[0022] The ethyl cellulose solution is evenly sprayed on the surface of the basalt fiber, and the mass ratio of the basalt fiber to the ethyl cellulose solution is 1:0.1-0.3. Then, the coated potassium carbonate is evenly sprayed, and the mass ratio of the basalt fiber to the coated potassium carbonate is 1:0.2-0.4. After drying, the modified basalt fiber is obtained.
[0023] By adopting the above technical scheme, basalt fiber, ethyl cellulose solution and coated potassium carbonate are matched together. The bonding effect of ethyl cellulose solution is utilized to make the coated potassium carbonate more stably bonded to the surface of basalt fiber. Ethyl cellulose is insoluble in water, which can further improve the waterproof and hydrophobic effects of the finished concrete and minimize the influence of moisture in the river channel on the mechanical strength of the concrete.
[0024] Preferably, the coated potassium carbonate is prepared by loading potassium carbonate onto perlite and then coating the surface with chitosan film liquid.
[0025] By adopting the above technical scheme, the porous perlite utilizes its multi-porous structure to facilitate the loading of potassium carbonate particles. After the loading is completed, the perlite is coated with chitosan film liquid to form a chitosan film on the surface of the porous perlite. The chitosan film has barrier properties and is insoluble in water. When algae in river water come into contact with concrete, the antibacterial effect of chitosan is utilized to inhibit the algae, and the algae on the concrete surface are removed in combination with the impact effect of the river water flow rate. Even if the algae attach to the concrete surface and metabolize to produce acid, the chitosan film is gradually destroyed by the acid, thereby gradually releasing potassium carbonate. Potassium carbonate can kill the algae on the concrete surface by its alkalinity and purify the water quality, thereby ensuring the strength of the concrete while extending the service life of the concrete.
[0026] Preferably, the water reducer is composed of polycarboxylic acid high-efficiency water reducer and calcium sugar in a mass ratio of 1:0.2-0.5.
[0027] By adopting the above technical scheme, polycarboxylic acid high-efficiency water reducing agent and sugar calcium are combined. On the one hand, their good water reducing property is utilized to improve the mechanical strength of concrete. On the other hand, sugar calcium has an inhibitory effect on the growth and reproduction of algae, which can further prevent the concrete surface from being corroded by algae.
[0028] In a second aspect, the present application provides a method for preparing fiber reinforced concrete, which adopts the following technical solution:
[0029] A method for preparing fiber reinforced concrete comprises the following steps:
[0030] S1. Weigh cement, modified aggregate, reinforcing fiber and filler, mix and stir evenly to prepare a primary mixture;
[0031] S2, weighing water, accelerating setting agent, water reducing agent and primary mixed material, mixing and stirring evenly to obtain a mixed material;
[0032] S3. The mixed material is sprayed and cured to obtain finished concrete.
[0033] By adopting the above technical scheme, the finished concrete can be quickly solidified on the slope protection after being sprayed onto the slope protection. When the river channel is filled with river water, the river water contacts the concrete, but the concrete itself has a dense structure and is not easy to penetrate water. Even if the river water contains acidic pollution sources, it is not easy to corrode the steel bars in the concrete and affect the strength of the concrete. At the same time, the surface of the concrete in contact with the river water is not easy to be attached to algae. Even if it is attached, it is easy to detach from the concrete surface under the impact of the river water. Even if the algae adhere to the concrete surface, it is not easy to reproduce. The concrete surface can even gradually inhibit and kill the attached algae, thereby making the slope protection concrete have a longer service life.
[0034] When people need to walk down from the slope to the bottom of the river to clean the river water and the river channel, the roughness of the concrete surface can protect the cleaners to arrive safely.
[0035] In summary, this application has the following beneficial effects:
[0036] 1. The modified aggregate and reinforcing fiber are matched, and the hydrophobic effect of hydrophobic titanium dioxide on the surface of the aggregate is utilized to make the concrete surface hydrophobic and anti-fouling, and it is not easy for algae to attach to the concrete surface; and titanium dioxide has good roughness. After attaching to the aggregate surface, it can further improve the roughness of the aggregate surface, so that the concrete surface has higher friction; at the same time, the addition of reinforcing fiber and the filling effect of hydrophobic titanium dioxide on the surface of the modified aggregate further improve the density of the concrete structure and make the concrete have higher strength; even if the slope protection concrete has been used for a long time, it is still not easy for algae to attach to the surface, thereby ensuring the mechanical strength of the concrete, and it has good friction, which can ensure the stable movement of people on the surface of the slope protection concrete.
[0037] 2. The perlite with open pores, potassium carbonate particles and chitosan membrane liquid are combined. When algae in river water come into contact with concrete, the antibacterial effect of chitosan is used to inhibit the algae, and the algae on the concrete surface are removed in combination with the impact effect of river water flow rate. Even if the algae attached to the concrete surface metabolize and produce acid, the chitosan membrane is gradually destroyed by the acid, thereby gradually releasing potassium carbonate. Potassium carbonate can kill the algae on the concrete surface with its alkalinity and purify the water quality, thereby ensuring the strength of the concrete while extending the service life of the concrete.
[0038] 3. Potassium carbonate particles are coated with chitosan film liquid. During the concrete mixing process, since chitosan is insoluble in water, the potassium carbonate particles will not be affected by the mixing water. Only when the algae in the river water metabolize and produce acid or the acid substances in the river water affect the concrete surface, the chitosan film will slowly dissolve and be destroyed. The gradually released potassium carbonate particles can further kill the algae on the concrete surface with their alkalinity after dissolution, preventing the concrete from being corroded by the acid produced by the algae metabolism. DETAILED DESCRIPTION
[0039] The present application is further described in detail below with reference to the embodiments.
[0040] Preparation example of modified aggregate
[0041] Preparation Example 1: The modified aggregate is prepared by the following method:
[0042] Weigh 1 kg of titanium dioxide and add it to 4 kg of silicone-acrylic emulsion and stir evenly. The particle size of titanium dioxide is 20 μm to obtain hydrophobic titanium dioxide.
[0043] 32.4kg of hydrophobic titanium dioxide is evenly sprayed on the surface of 900kg of aggregate. The aggregate is composed of 420kg of crushed stone and 480kg of medium sand. The particle size of the crushed stone is 5-25mm with continuous grading and mud content <1%. The medium sand is medium sand in zone II with an apparent density of 2660kg / m 3 , fineness modulus is 2.5, mud content is <1.0%; after drying and dispersing until the aggregates do not agglomerate and stick to each other, the finished product is obtained.
[0044] Preparation Example 2: This preparation example differs from Preparation Example 1 in that:
[0045] Weigh 1 kg of titanium dioxide and add it to 3 kg of silicone-acrylic emulsion and stir evenly. The particle size of titanium dioxide is 20 μm to obtain hydrophobic titanium dioxide.
[0046] 8 kg of hydrophobic titanium dioxide was evenly sprayed on the surface of 800 kg of aggregate, the aggregate was composed of 360 kg of crushed stone and 440 kg of medium sand, and the finished product was obtained after drying and dispersion until the aggregates did not agglomerate and adhere to each other.
[0047] Preparation Example 3: This preparation example differs from Preparation Example 1 in that:
[0048] Weigh 1 kg of titanium dioxide and add it to 5 kg of silicone-acrylic emulsion and stir evenly. The particle size of titanium dioxide is 20 μm to obtain hydrophobic titanium dioxide.
[0049] 50kg of hydrophobic titanium dioxide is evenly sprayed on the surface of 1000kg of aggregate, the aggregate is composed of 480kg of crushed stone and 520kg of medium sand, and the finished product is obtained after drying and dispersion until the aggregates do not agglomerate and adhere to each other.
[0050] Preparation example of modified carbon fiber
[0051] Preparation Example 4: The modified carbon fiber is prepared by the following method:
[0052] After heating and melting rosin glycerol ester, a rosin glycerol ester melt is obtained;
[0053] 1 kg of graphene was uniformly dispersed in 6 kg of rosin glycerol ester melt, and the graphene particle size was 20 μm to prepare a composite liquid;
[0054] 1 kg of the composite liquid was weighed and sprayed evenly onto the surface of 3.5 kg of carbon fiber with a carbon fiber length of 2 mm. The modified carbon fiber was obtained by drying and dispersing until there was no carbon fiber agglomeration.
[0055] Preparation Example 5: The modified carbon fiber is prepared by the following method:
[0056] After heating and melting rosin glycerol ester, a rosin glycerol ester melt is obtained;
[0057] 1 kg of graphene was uniformly dispersed in 4 kg of rosin glycerol ester melt, and the graphene particle size was 20 μm to prepare a composite liquid;
[0058] 1 kg of the composite liquid was weighed and sprayed evenly onto the surface of 2 kg of carbon fiber, the length of the carbon fiber was 2 mm, and the modified carbon fiber was obtained by drying and dispersing until there was no carbon fiber agglomeration.
[0059] Preparation Example 6: The modified carbon fiber is prepared by the following method:
[0060] After heating and melting rosin glycerol ester, a rosin glycerol ester melt is obtained;
[0061] 1 kg of graphene was uniformly dispersed in 7 kg of rosin glycerol ester melt, and the graphene particle size was 20 μm to prepare a composite liquid;
[0062] 1 kg of the composite liquid was weighed and sprayed evenly onto the surface of 5 kg of carbon fiber, the length of the carbon fiber was 2 mm, and the modified carbon fiber was obtained by drying and dispersing until there was no carbon fiber agglomeration.
[0063] Preparation Example of Coated Potassium Carbonate
[0064] Preparation Example 7: Coated potassium carbonate was prepared by the following method:
[0065] Weigh 1 kg of perlite with open pores and disperse it in 10 kg of a 40% potassium carbonate aqueous solution, wherein the particle size of the perlite with open pores is 40 meshes. Stir at a speed of 500 r / min for 15 minutes, then let it stand for 5 minutes, filter out the perlite with open pores, and freeze-dry it to obtain loaded perlite.
[0066] Weigh 1 kg of chitosan and place it in 97 kg of 1% by mass dilute acetic acid solution, stirring and dissolving, the deacetylation degree of chitosan is 98%, then add 2 kg of glycerol, mix well, and prepare chitosan film liquid;
[0067] 0.2 kg of chitosan film liquid was evenly sprayed on the surface of 1 kg of perlite, and the finished coated potassium carbonate was obtained after drying and dispersion until the perlite loaded thereon did not agglomerate and adhere to each other.
[0068] Preparation example of modified basalt fiber
[0069] Preparation Example 8: Modified basalt fiber is prepared by the following method:
[0070] 0.2 kg of ethyl cellulose solution was evenly sprayed on the surface of 1 kg of basalt fiber, the basalt fiber length was 2 mm, and the ethyl cellulose solution was a 1% by mass ethyl cellulose ethanol solution. Then 0.32 kg of coated potassium carbonate prepared in Preparation Example 7 was evenly sprayed on the surface. After drying, modified basalt fiber was obtained.
[0071] Preparation Example 9: Modified basalt fiber is prepared by the following method:
[0072] 0.1 kg of ethyl cellulose solution was evenly sprayed on the surface of 1 kg of basalt fiber, the basalt fiber length was 2 mm, and the ethyl cellulose solution was a 1% by mass ethyl cellulose ethanol solution. Then 0.2 kg of coated potassium carbonate prepared in Preparation Example 7 was evenly sprayed on the surface. After drying, modified basalt fiber was obtained.
[0073] Preparation Example 10: Modified basalt fiber is prepared by the following method:
[0074] 0.3 kg of ethyl cellulose solution was evenly sprayed on the surface of 1 kg of basalt fiber, the basalt fiber length was 2 mm, and the ethyl cellulose solution was a 1% by mass ethyl cellulose ethanol solution. Then 0.4 kg of coated potassium carbonate prepared in Preparation Example 7 was evenly sprayed on the surface. After drying, modified basalt fiber was obtained.
[0075] Example
[0076] Example 1: A fiber reinforced concrete:
[0077] 238kg cement, 900kg modified aggregate, 128kg water, 6.5kg accelerator, 5kg water reducer, 15kg reinforcing fiber, 15kg filler; the cement is ordinary Portland cement with a P.O42.5, the modified aggregate is the modified aggregate prepared in Preparation Example 1, the accelerator is GQ-SN02 accelerator, the water reducer is composed of polycarboxylic acid high-efficiency water reducer and sugar calcium in a mass ratio of 1:0.4, and the reinforcing fiber is composed of modified The carbon fiber and the modified basalt fiber are composed, the modified carbon fiber is selected from the modified carbon fiber prepared in Preparation Example 4, and the modified basalt fiber is selected from the modified basalt fiber prepared in Preparation Example 8; the filler is composed of hydrophobic silica and hydrogenated terpene resin in a mass ratio of 1:0.2, the particle size of the hydrogenated terpene resin is 40 mesh, the silica is placed in KH-570 and stirred and soaked, the silica particle size is 40 mesh, and then the silica is taken out and dried to obtain the hydrophobic silica;
[0078] The preparation method is as follows:
[0079] S1. Weigh cement, modified aggregate, reinforcing fiber and filler, mix and stir evenly to prepare a primary mixture;
[0080] S2, weighing water, accelerating setting agent, water reducing agent and primary mixed material, mixing and stirring evenly to obtain a mixed material;
[0081] S3. The mixed material is sprayed and cured to obtain finished concrete.
[0082] Embodiment 2: This embodiment differs from Embodiment 1 in that:
[0083] 200kg cement, 800kg modified aggregate, 100kg water, 5kg accelerator, 4kg water reducer, 10kg reinforcing fiber and 10kg filler; the cement is ordinary Portland cement with a P.O42.5, the modified aggregate is the modified aggregate prepared in Preparation Example 2, the accelerator is GQ-SN02 accelerator, the water reducer is composed of a polycarboxylic acid high-efficiency water reducer and calcium sugar in a mass ratio of 1:0.2, the reinforcing fiber is composed of a modified carbon fiber and a modified basalt fiber in a mass ratio of 1:1, the modified carbon fiber is the modified carbon fiber prepared in Preparation Example 5, and the modified basalt fiber is the modified basalt fiber prepared in Preparation Example 9.
[0084] Embodiment 3: This embodiment differs from Embodiment 1 in that:
[0085] 260kg cement, 1000kg modified aggregate, 140kg water, 10kg accelerator, 6kg water reducer, 18kg reinforcing fiber and 20kg filler; the cement is ordinary Portland cement with a P.O42.5, the modified aggregate is the modified aggregate prepared in Preparation Example 3, the accelerator is GQ-SN02 accelerator, the water reducer is composed of a polycarboxylic acid high-efficiency water reducer and calcium sugar in a mass ratio of 1:0.5, the reinforcing fiber is composed of a modified carbon fiber and a modified basalt fiber in a mass ratio of 1:3, the modified carbon fiber is the modified carbon fiber prepared in Preparation Example 6, and the modified basalt fiber is the modified basalt fiber prepared in Preparation Example 10.
[0086] Embodiment 4: This embodiment differs from Embodiment 1 in that:
[0087] During the preparation of modified aggregate, the silicone-acrylic emulsion is replaced by an equal amount of sodium alginate in the raw materials.
[0088] Embodiment 5: This embodiment differs from Embodiment 1 in that:
[0089] In the reinforcing fiber raw materials, the modified carbon fiber is replaced by the carbon fiber of the same mass, and the modified basalt fiber is replaced by the basalt fiber of the same mass.
[0090] Embodiment 6: This embodiment differs from Embodiment 1 in that:
[0091] The modified carbon fiber is replaced by carbon fiber of equal quality in the reinforcing fiber raw material.
[0092] Embodiment 7: This embodiment differs from Embodiment 1 in that:
[0093] The modified basalt fiber is replaced by basalt fiber of equal quality in the reinforcing fiber raw material.
[0094] Embodiment 8: This embodiment differs from Embodiment 1 in that:
[0095] During the preparation of modified carbon fiber, the rosin glycerol ester melt is replaced by an equal mass of sodium alginate in the raw material.
[0096] Embodiment 9: This embodiment differs from Embodiment 1 in that:
[0097] During the preparation of modified basalt fiber, the ethyl cellulose solution is replaced by an equal mass of sodium carboxymethyl cellulose solution in the raw material.
[0098] Embodiment 10: This embodiment differs from Embodiment 1 in that:
[0099] During the preparation of modified basalt fiber, no coated potassium carbonate was added to the raw materials.
[0100] Embodiment 11: This embodiment differs from Embodiment 1 in that:
[0101] In the preparation process of modified basalt fiber coated potassium carbonate, the chitosan membrane solution is replaced by an equal mass of ethyl cellulose solution in the raw material.
[0102] Embodiment 12: This embodiment differs from Embodiment 1 in that:
[0103] The filler is silicon dioxide.
[0104] Comparative Example
[0105] Comparative Example 1: The difference between this comparative example and Example 1 is that:
[0106] The modified aggregate is replaced by aggregate of equal mass in the raw materials.
[0107] Comparative Example 2: The difference between this comparative example and Example 1 is that:
[0108] No reinforcing fibers are added to the raw materials.
[0109] Performance testing
[0110] 1. Compressive strength
[0111] Finished concrete was prepared by the preparation methods of Examples 1-12 and Comparative Examples 1-2, standard test blocks were made with reference to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the compressive strength of the test blocks after 28 days of curing was measured and the data was recorded.
[0112] 2. Anti-permeability The finished concrete was prepared by the preparation method of Examples 1-12 and Comparative Examples 1-2. The water seepage depth of the standard test block was tested by the step-by-step pressurization method in accordance with GB / T50082-2019 "Standard for Test Methods for Long-term Properties and Durability of Ordinary Concrete", and the data was recorded.
[0113] 3. Friction performance
[0114] Finished concrete was prepared by the preparation method of Examples 1-3, and sprayed on a river slope with an inclination of 45°. After curing for 28 days, the test volunteers stood on the river slope and moved downward. The movement stability was scored. The scoring criteria were as follows: stable movement, no relative sliding phenomenon, and the ability to stop at any position 10 points → obvious relative sliding, it is easy to rush directly from the top of the 45° slope to the bottom of the river quickly, and it is impossible to stop halfway 0 points; a higher score and better anti-slip performance indicate a higher friction.
[0115] 4. Resistance to algae adhesion and corrosion
[0116] Finished concrete was prepared by the preparation methods of Examples 1-12 and Comparative Examples 1-2. A standard test block was made with reference to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". Half of the test block was immersed in river water. There were 1×10 6 The algae were soaked in river water with a flow rate of 1.5 m / s, a temperature of 30°C, sufficient oxygen content and ventilation for 60 days. Then the samples were taken out and the algae attachment area on the surface of the samples was observed. The unit is mm 2 ; Record the data of Examples 1-12 and Comparative Example 1; Remove the algae on the surface of the sample after algae treatment, and refer to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" again to test the compressive strength, and record the data of Examples 1-12 and Comparative Example 1-2.
[0117] Table 1 Performance test table
[0118]
[0119]
[0120] It can be seen from Examples 1-3 and Table 1 that the concrete prepared in the present application has high strength and good anti-seepage effect, and has good friction, is non-slip on the slope protection, and is not easy to attach algae. Even if algae attach to the surface of the concrete, it is not easy to corrode the concrete and affect the mechanical strength of the concrete.
[0121] Combining Example 1 and Examples 4-12 and Table 1, it can be seen that in the preparation process of the modified aggregate in Example 4, the silicone-acrylic emulsion is replaced by an equal mass of sodium alginate in the raw materials. Compared with Example 1, the compressive strength of the concrete prepared in Example 4 is slightly less than that in Example 1, the water seepage depth is greater than that in Example 1, the algae attachment area is greater than that in Example 1, and the difference between the compressive strength without algae treatment and the compressive strength after algae treatment is greater than the corresponding difference in Example 1; this shows that sodium alginate is hydrophilic and water-retaining. During the hydration process of concrete, the mixing water is not easily evaporated, resulting in the strength of the concrete being affected, and sodium alginate is hygroscopic and easily absorbs moisture in river water, resulting in moisture entering the internal structure of the concrete and affecting the strength of the concrete; the silicone-acrylic emulsion in the present application has good hydrophobicity and stain resistance, which can not only prevent moisture from entering the internal structure of the concrete, but also avoid the attachment of algae to the concrete surface as much as possible, thereby making the concrete less susceptible to the corrosion of algae in the river water.
[0122] In Example 5, the modified carbon fiber is replaced by the same mass of carbon fiber in the reinforcing fiber raw material, and the modified basalt fiber is replaced by the same mass of basalt fiber. In Example 6, the modified carbon fiber is replaced by the same mass of carbon fiber in the reinforcing fiber raw material, and the modified basalt fiber is replaced by the same mass of basalt fiber in the reinforcing fiber raw material of Example 7. Compared with Example 1, the compressive strength of concrete prepared in Examples 5, 6, and 7 is slightly less than that in Example 1, the water seepage depth is greater than that in Example 1, the algae attachment area is greater than that in Example 1, and the difference between the compressive strength without algae treatment and the compressive strength after algae treatment is greater than the corresponding difference in Example 1; it indicates that the carbon fiber treated with rosin glycerol ester and graphene, combined with ethyl cellulose solution and coated potassium carbonate treated basalt fiber, can not only improve the hydrophobic effect of the internal structure of concrete, but also improve the strength of concrete, while making it difficult for algae to adhere to the surface of concrete, and even if algae are attached, it can inhibit and kill the algae, and prevent the algae from metabolizing and producing acid to affect the mechanical strength of concrete.
[0123] In the preparation process of modified carbon fiber in Example 8, the rosin glycerol ester melt was replaced by an equal mass of sodium alginate in the raw material. In the preparation process of modified basalt fiber in Example 9, the ethyl cellulose solution was replaced by an equal mass of sodium carboxymethyl cellulose solution in the raw material. Compared with Example 1, the water seepage depth of concrete prepared in Examples 8 and 9 was greater than that in Example 1, the algae attachment area was greater than that in Example 1, and the difference between the compressive strength without algae treatment and the compressive strength after algae treatment was greater than the corresponding difference in Example 1; it indicates that although sodium alginate solution and sodium carboxymethyl cellulose solution are viscous, they are hydrophilic and hygroscopic, which can easily affect the water penetration resistance of concrete, resulting in the mechanical strength of concrete being affected, and algae are easily attached, affecting the strength of concrete.
[0124] In the preparation process of the modified basalt fiber in Example 10, no coated potassium carbonate was added to the raw materials. In the preparation process of the coated potassium carbonate in the modified basalt fiber in Example 11, the chitosan film liquid was replaced by an ethyl cellulose solution of equal mass in the raw materials. Compared with Example 1, the compressive strength of the concrete prepared in Example 10 was less than that in Example 1, and the water seepage depth was greater than that in Example 1. The algae attachment area of the concrete prepared in Examples 10 and 11 was greater than that in Example 1, and the difference between the compressive strength without algae treatment and the compressive strength after algae treatment was greater than the corresponding difference in Example 1; it indicates that the chitosan on the surface of the coated potassium carbonate can firstly inhibit the growth of algae, and as time goes on, even if the algae and other organisms metabolize to produce acid, the chitosan is gradually dissolved, but the potassium carbonate particles coated inside can be gradually released, and the algae attached to the concrete surface are further killed by the alkalinity after the potassium carbonate particles are dissolved, thereby minimizing the corrosion of the concrete by algae and affecting its mechanical strength.
[0125] The filler in Example 12 is silicon dioxide. Compared with Example 1, the water penetration depth of the concrete prepared in Example 12 is greater than that in Example 1, the algae attachment area is greater than that in Example 1, and the difference between the compressive strength before algae treatment and the compressive strength after algae treatment is greater than the corresponding difference in Example 1; this indicates that the hydrophobic silicon dioxide and the hydrogenated terpene resin are combined to further improve the impermeability of the concrete by utilizing the particle filling effect of silicon dioxide in combination with its hydrophobic effect and the water barrier property of the hydrogenated terpene resin, and in the process of concrete hydration, since the melting point of the hydrogenated terpene resin is about 38°C, it is easily melted by the hydration temperature, thereby improving the density of the internal structure of the concrete, and making the finished concrete have better mechanical strength.
[0126] Combining Example 1 and Comparative Examples 1-2 and Table 1, it can be seen that the modified aggregate in the raw material of Comparative Example 1 is replaced by aggregate of equal mass, and no reinforcing fiber is added to the raw material of Comparative Example 2. Compared with Example 1, the compressive strength of concrete prepared by Comparative Examples 1 and 2 is less than that of Example 1, the water seepage depth is greater than that of Example 1, the algae attachment area of Comparative Example 1 is greater than that of Example 1, and the difference between the compressive strength of Comparative Examples 1 and 2 without algae treatment and the compressive strength after algae treatment is greater than the corresponding difference in Example 1; it indicates that the treatment of aggregate with hydrophobic titanium dioxide can not only improve the surface roughness of concrete, but also improve the strength of concrete, and utilize its hydrophobic effect to further prevent algae from attaching to the concrete surface and affecting the mechanical strength of concrete.
[0127] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A fiber reinforced concrete, characterized in that: The invention is prepared from the following raw materials in parts by weight: 200-260 parts of cement, 800-1000 parts of modified aggregate, 100-140 parts of water, 5-10 parts of accelerating agent, 4-6 parts of water reducing agent, 10-18 parts of reinforcing fiber and 10-20 parts of filler; the modified aggregate is prepared by coating the surface of the aggregate with hydrophobic titanium dioxide; The modified aggregate is prepared by the following method: Weigh titanium dioxide in a mass ratio of 1:3-5 and add it to the silicone-acrylic emulsion, mix and stir evenly to obtain hydrophobic titanium dioxide; spray the hydrophobic titanium dioxide evenly on the surface of the aggregate, the mass ratio of the hydrophobic titanium dioxide to the aggregate is 1-5:100, dry and disperse, and obtain a finished product; The reinforcing fiber is composed of modified carbon fiber and modified basalt fiber in a mass ratio of 1:1-3; The modified carbon fiber is prepared by the following method: After hot melting the rosin glycerol ester, a rosin glycerol ester melt is obtained; The graphene is evenly dispersed in a rosin glycerol ester melt at a mass ratio of 1:4-7 to prepare a composite liquid; The composite liquid is uniformly sprayed onto the surface of the carbon fiber at a mass ratio of 1:2-5, and the modified carbon fiber is obtained after drying and dispersion; The modified basalt fiber is prepared by the following method: Ethyl cellulose solution is evenly sprayed on the surface of basalt fiber, the mass ratio of basalt fiber to ethyl cellulose solution is 1:0.1-0.3, and then coated potassium carbonate is evenly sprayed, the mass ratio of basalt fiber to coated potassium carbonate is 1:0.2-0.4, and after drying, modified basalt fiber is obtained; the coated potassium carbonate is obtained by coating the surface of open-pored perlite with chitosan film liquid after potassium carbonate is loaded.
2. A fiber reinforced concrete according to claim 1, characterized in that: The water reducer is composed of a polycarboxylic acid high-efficiency water reducer and calcium sugar in a mass ratio of 1:0.2-0.
5.
3. A method for preparing fiber reinforced concrete according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1. Weigh cement, modified aggregate, reinforcing fiber and filler, mix and stir evenly to prepare a primary mixture; S2, weighing water, accelerating setting agent, water reducing agent and primary mixed material, mixing and stirring evenly to obtain a mixed material; S3. The mixed material is sprayed and cured to obtain finished concrete.
